Trees in Anglo-Saxon England : literature, lore and landscape - Hooke, Della (Anglo-Saxon Studies, 13., 2010)
Trees played a particularly important part in the rural economy of Anglo-Saxon England, both for wood and timber and as a wood-pasture resource, with hunting gaining a growing cultural role. But they are also powerful icons in many pre-Christian religions, with a degree of tree symbolism found in Christian scripture too. This wide-ranging book explores both the real historical and archaeological evidence of trees and woodland, and as they are depicted in Anglo-Saxon literature and legend.